Caracterização da família Bromeliaceae em uma região de mata úmida do cristalino no estado do Ceará - Freitas, Mateus de Sousa (2023)
The Bromeliaceae family has a predominantly neotropical distribution, occurring in Brazil mainly in the Atlantic Forest domain, as well as in remnants of humid forest in the semi-arid northeast. Bromeliads are characterized by their spiral phyllotaxis, which forms tanks, or phytotelms, in which they can remain filled with water all year round or partially. These ponds are important microhabitats for various species of fauna and microfauna. The ecosystem services provided by this plant group are varied, which reinforces its ecological importance, making effective conservation necessary. With this in mind, the aim of this study was to carry out an inventory of Bromeliaceae in a wet forest region of the Ceará crystalline, located between the municipalities of Maranguape and Caucaia. The data was obtained in the field using the usual techniques for collecting, recording and herborizing plants, which were then deposited in the EAC herbarium. For distribution data, maps were drawn up in ArqGis, combining data collected in the field, data available on the speciesLink and MapBiomas platforms and survey work available in the literature. For a review of the conservation status of local bromeliads, the status for all the species collected was presented, in addition to generating the conservation status data itself based on the adaptation of criteria pre-established by past studies, such as knowledge of the species in virtual herbarium databases; size of the distribution area; distribution in biomes; environmental changes; and the density of the species throughout the distribution area. Twelve species were identified, distributed in 6 genera (Aechmea, Guzmania, Racinaea, Tillandsia, Vriesea and Wittmackia), identified based on specialized literature and the help of specialists in the family. An identification key for the species was drawn up, using floral and vegetative morphological characters. Aechmea aquilega was the most abundant and least threatened species, while the genus Guzmania with G. lingulata, G. monostachia and G. sanguinea ranged from low risk to presumed threatened and 'Endangered', respectively. Racinaea spiculosa was the only one of its kind present in the study area and, although it is not very threatened, it is the only region in Ceará to harbor it due to its local endemism. The Tillandsia species stood out for their rarity within the collection transect, all of them being outside the threat levels in the literature, but potentially endangered in the humid forest of the Serra de Maranguape and Serra da Rajada. Vriesea and Wittmackia have species that are endemic to the state of Ceará and, consequently, high levels of threat. Thus, the work provides data that will help in future taxonomic studies, as well as justifying efforts for more effective conservation of the regions studied in order to preserve these very sensitive species in their natural habitat with a history of extreme devastation and disturbance.